Measuring urban sprawls on highway strip parameters using GIS approach. - Hj. Mohd. Noor, Norzailawati; Myint, Khin Cho (2012)
Urban sprawl is one of the contemporary issues of cities all over the world nowadays, contributes to the inefficient use of land resources, energy and large scale absorption of open space that can otherwise be used more effectively for a land use development activities. It is refers to a specific form of urban development characterized by low-density, leapfrog, highway strip development and discontinuity. Highway strip is one of the spatial factors for urban sprawl, which usually characterized by fast food restaurants and retail strip malls and including single family housing units lining rural highway. This research attempt to study a remote sensing and GIS approach to measure spatial factor on highway strip for urban sprawls to assess the characteristic of expansion of land use sprawl particularly for residential, commercial, industrial areas and identify either the development exactly was sprawl or common development. The analysis shows a highway strip indicator was calculated by measuring the distance from the highways buffer to the residential unit. Finally, further understanding of dynamic phenomenon urban sprawl which is, highway strip pattern and measurement of sprawl indicator was determined.